The Wes Anderson collection - Seitz, Matt Zoller; Anderson, Wes 1969- (New York Abrams, 2013)
Wes Anderson is one of the most influential voices from the past two decades of American cinema. A true auteur, Anderson is known for the visual artistry, inimitable tone, and idiosyncratic characterizations that make each of his films- 'Bottle Rocket', 'Rushmore', 'The Royal Tenenbaums', 'The Life Aquatic with Steve Zissou', 'The Darjeeling Limited', 'Fantastic Mr. Fox', and 'Moonrise Kingdom'- instantly recognizable as "Andersonian." 'The Wes Anderson Collection' is the first in-depth overview of Anderson's filmography, guiding readers through his life and career. Previously unpublished photos, artwork, and ephemera complement a book-length conversation between Anderson and award-winning critic Matt Zoller Seitz. The interview and images are woven together in a meticulously designed book that captures the spirit of his films: melancholy and playful, wise and childish - and thoroughly original.
Introduction -- Preface -- Bottle Rocket -- Rushmore -- The Royal Tenenbaums -- The Life Aquatic with Steve Zissou -- The Darjeeling Limited -- Fantastic Mr. Fox -- Moonrise Kingdom.
Essays, interviews, and photographs covering Mr. Anderson's overall career and specific films.
Includes index.
Keywords: Anderson, Wes -- 1969- -- Interviews; Motion picture producers and directors -- United States